Elevated high-sensitivity C-reactive protein levels are associated with intracranial arterial stenosis in elderly patients - Mimi Li; Shufen Liu; Chunnuan Chen (BMC Neurology)
Abstract Background To determine the correlation between intracranial atherosclerotic stenosis and high-sensitivity C-reactive protein (hs-CRP) levels in elderly patients with cerebral infarction. Methods We performed a retrospective assessment of acute minor ischemic stroke patients aged over 60 at our institution from January 2021 to May 2023. A thorough computed tomography angiography (CTA) assessment was conducted for each participant. The patients were classified into four categories according to the site of stenosis in the cerebral arteries: (1) intracranial atherosclerotic stenosis (ICAS), (2) extracranial atherosclerotic stenosis (ECAS), (3) combined intracranial and extracranial atherosclerotic stenosis (IEAS), and (4) non-arterial stenosis (NOAS). Multivariate logistic regression analysis was utilized to evaluate the relationship between intracranial atherosclerotic stenosis and hs-CRP levels. The predictive efficacy of hs-CRP for intracranial arterial stenosis was assessed utilizing the Receiver Operating Characteristic (ROC) curve. Results The research comprised 203 participants in total. Among these, 73 individuals (34.96%) were categorized as having Intracranial Stenosis Atherosclerosis (ICAS). The hs-CRP levels in the ICAS group were markedly elevated (P = 0.011), while no significant difference in hs-CRP levels was observed between the ECAS and NOAS groups (P = 0.080). Hs-CRP levels were found to be independently correlated with intracranial arterial stenosis (OR 1.136, 95% CI 1.038–1.242, P = 0.006) following multivariable analysis, as shown in Table 2. The upper quartile of hs-CRP was determined to be a statistically significant independent risk factor for intracranial stenosis (OR 3.779, 95% CI 1.519–9.402, P = 0.004). The area under the curve (AUC) for hs-CRP was calculated to be 0.632 following the analysis of the ROC curve. The ideal cutoff value for hs-CRP was established at 3.96 mg/L, accompanied by a 95% confidence interval ranging from 0.555 to 0.710 (P = 0.001). The sensitivity and specificity were 0.500 and 0.735, respectively. Conclusions In elderly patients with acute minor ischemic stroke, elevated hs-CRP levels are significantly correlated with intracranial atherosclerosis stenosis, rather than extracranial atherosclerotic stenosis.